Analisis Keselamatan dan Kesehatan Kerja di Akademi Metrologi dan Instrumentasi - Nandang Gunawan Tunggal Waras; Dudi Adi Firmansyah; Budi Yasri (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Occupational Safety and Health (K3) is an effort to create a safe, healthy and prosperous work environment, free from accidents, fires, explosions, environmental pollution and work-related diseases. Work accidents can cause losses for workers, employers, government and society, which can include loss of human life, damage to property and the environment. For this reason, concrete steps need to be taken to prevent and reduce the occurrence of work accidents as much as possible. One of the conditions where work accidents can occur is in the educational environment. The research uses descriptive methods with the aim of identifying the types of work accidents and how to overcome them that can occur. Based on the research results, it was concluded that occupational safety and health are very important, potential accidents in the Akmet environment can be identified. By using the HIRADC method, potential hazards can be identified and controls that must be implemented, such as using elimination methods to creating a quality manual and creating procedures for academic activities. This research has produced a draft Quality Guide for Occupational Safety and Health as well as procedures for academic activities in the Akmet environment.